Legal Analysis Of Copyright Issues In Youtube Content Reviewed From Law Number 28 Of 2014 On Copyright - Yudo Kamaru (Estudiante Law Journal, 2019)
Abstract: The purpose of this study is to know the concept of copyright protection in YouTube according to Law No. 28 of 2014 on Copyright and Knowing and analyzing the factors that cause many cases of copyright infringement in YouTube Content. The type of research used by researchers in compiling this research is a type of normative research using 2 (two) approaches, namely the Regulatory Approach and the case approach, and the Comparison Approach. The results of this study show that:  First, That The Protection of Copy Right In Youtube According to Law No. 28 of 2014 on Copyright for creators whose video works are re-uploaded (reuploaded)on  YouTube illegally obtained when violating the moral and or economic rights of the creator or holder of the video in the form of preventive legal protection and legal protection  Repressive. Preventive legal protection is obtained by registering the creation to the Content ID feature on  YouTube and also registered with the Directorate General of Intellectual Property. Repressive legal protection is obtained in the form of freedom of choice of dispute resolution path either non-litigation path or litigation path.  Second, that factors that affect the number of people who commit copyright infringement or in the context of this research are violations of copyrights in Youtube content, namely:  Legal Factors, Economic Pressure Factors, Cultural Factors, Education Factors, Weak Factors in law enforcement against copyright infringement perpetrators and Lack of Public Understanding of Copyright Protection.Keyword: CopyRight; Youtube; Copyright.